Glyphosate and the key characteristics of an endocrine disruptor: A review. (May 2021) - Muñoz, Juan P.; Bleak, Tammy C.; Calaf, Gloria M.
Abstract: Glyphosate is a large-spectrum herbicide that was introduced on the market in 1974. Due to its important impact on the crop industry, it has been significantly diversified and expanded being considered the most successful herbicide in history. Currently, its massive use has led to a wide environmental diffusion and its human consumption through food products has made possible to detect it in urine, serum, and breast milk samples. Nevertheless, recent studies have questioned its safety and international agencies have conflicting opinions about its effects on human health, mainly as an endocrine-disrupting chemical (EDC) and its carcinogenic capacity. Here, we conduct a comprehensive review where we describe the most important findings of the glyphosate effects in the endocrine system and asses the mechanistic evidence to classify it as an EDC. We use as guideline the ten key characteristics (KCs) of EDC proposed in the expert consensus statement published in 2020 (La Merrill et al., 2020) and discuss the scopes of some epidemiological studies for the evaluation of glyphosate as possible EDC. We conclude that glyphosate satisfies at least 8 KCs of an EDC, however, prospective cohort studies are still needed to elucidate the real effects in the human endocrine system. Highlights: Glyphosate is the active component of the most commonly used herbicide in the world. There is conflicting evidence regarding the effects of glyphosate in the endocrine system. This is the first review that consolidates the mechanistic evidence on glyphosate as endocrine-disrupting chemical (EDC). Glyphosate satisfies at least 8 key characteristics of an EDC. Prospective cohort studies are needed in order to elucidate whether glyphosate is an EDC.